DEVELOPMENT OF METACOGNITIVE AND SOCIO-AFFECTIVE STRATEGIES IN EFL CLASSES AT SECONDARY SCHOOLS - Žindžiuvienė, Ingrida Eglė (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The article focuses on the development of learning strategies during the process of foreign language learning. With the obvious implementation of cognitive learning strategies, the development of other types of strategies, metacognitive and socio-affective, remains an urgent issue. Very often these latter strategies are either disregarded or dismissed during the language learning process. However, recent studies have pointed out the necessity for the development of all types of learning strategies and their implementation at an early stage of learning. Therefore, the aim of this research is to determine the scope of the development of metacognitive and socio-affective learning strategies during the process of foreign language learning. Quantitative and qualitative methods have been used to determine the frequency and mode of the above-mentioned types of learning strategies during the process of teaching and learning English as a foreign language (EFL). Two hypotheses have been raised: (1) Metacognitive strategies are often disregarded in the process of language learning in the classes for adolescents; (2) The potential of implementation of socio-affective strategies in EFL classes is underestimated in the process of language learning in the classes for adolescents. The object of the research consists of 12 selected EFL textbooks and activities included in them. The research results prove the fact that much more attention to metacognitive learning strategy development is needed during EFL classes, as these strategies strongly benefit the overall process of language acquisition. To compare, socio-affective learning strategies are more often implemented during EFL classes; however, their development is rather unsystematic.